An Analytical Study of Women Empowerment in the Economy of Karnataka from the Perspective of Dr. B. R. Ambedkar - Rekha Kittur; Kannakappa Pujar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Dr. Bhimrao Ambedkar’s progressive vision of women’s empowerment is highly relevant. Ambedkar strongly opposed practices such as child marriage, commodification of women and forced labor. He stressed the importance of education, economic independence and active participation of women in all aspects of society. This research paper examines Dr. Ambedkar’s contributions to improving the status of women, focusing on their self-reliance, economic participation and legal rights. The study highlights his belief in challenging patriarchal structures and uplifting the family economy to achieve gender equality. It underlines the significance of his ideas in addressing contemporary challenges of gender inequality and social justice.
Keywords: Dr. B. R. Ambedkar; Economic Progress; Women Empowerment